Pengembangan dan Validasi Metode Bioanalisis Trimetoprim dalam Sampel Plasma dan Urin Manusia Simulasi Menggunakan KCKT-PDA - Notario, Dion; Amelia, Jessica; Della, Genoveva (Jurnal Kefarmasian Indonesia, 2023)
To monitor trimethoprim levels (TMP) in humans, a validated, simple, and cost-efficient analytical method is needed to be applied regularly. However, most of the methods used to establish TMP levels in urine and plasma use complex instrumentation. Therefore, in this study, a simpler High-Performance Liquid Chromatography-based (HPLC) method was developed. The separation was carried out using a GIST® C18 column (150 × 4.6 mm, 5 μm) at a temperature of 35°C which was fed by a mobile phase in the form of an acetic acid solution pH 2.5: acetonitrile (87:13, v / v) at a speed of 1.4 ml/min. Detection was performed with Photodiode Array Detector (PDA) at wavelengths of 254 nm and 243 nm to quantify TMP in urine and plasma samples respectively. The preparation of urine and plasma sequentially was carried out by the liquid-liquid extraction (ECC) method using ethyl acetate and the protein precipitation using acetonitrile. This method proved to be selective, linear (R=0.997), accurate with %error ≤ 10.29% at LLOQ level and above LLOQ value %error ≤ 10.45%, precision with %RSD ≤ 11.79% at LLOQ level and %RSD ≤ 10.82% above LLOQ. In addition, this method is quite sensitive for pharmacokinetic studies in the urine and monitoring of TMP levels in the blood with LLOQ 5 mg/L in both urine and plasma. The stability of trimethoprim in solution, urine, and plasma was conducted to ensure storage time. The developed method is proven to be valid and can be applied in pharmacokinetic studies and monitoring of trimethoprim drug levels in urine and plasma.